Evidence That Cingulin Regulates Endothelial Barrier Function In Vitro and In Vivo. Issue 4 (April 2016) - Schossleitner, Klaudia; Rauscher, Sabine; Gröger, Marion; Friedl, Heinz Peter; Finsterwalder, Richard; Habertheuer, Andreas; Sibilia, Maria; Brostjan, Christine; Födinger, Dagmar; Citi, Sandra; Petzelbauer, Peter
Abstract : Objective—: Cingulin is a cytoplasmic component of tight junctions. Although modulation of cingulin levels in cultured epithelial model systems has no significant effect on barrier function, evidence from cingulin knockout mice suggests that cingulin may be involved in the regulation of the behavior of epithelial or endothelial cells. Here, we investigate the role of cingulin in the barrier function of endothelial cells. Approach and Results—: We show that cingulin is expressed in human endothelial cells of the skin, brain, and lung in vivo and in vitro. Endothelial cingulin colocalizes and coimmunoprecipitates with the tight junction proteins zonula occludens-1 and guanine nucleotide exchange factor-H1. Cingulin overexpression in human umbilical vein endothelial cell induces tight junction formation, increases transendothelial electric resistance, and strengthens barrier function for low and high molecular weight tracers. In contrast, cultured endothelial cells lacking cingulin are more permeable for low molecular weight tracers. In cingulin knockout mice, neurons of the area postrema and Purkinje cells show an increased uptake of small molecular weight tracers indicating decreased barrier function at these sites. Conclusions—: We demonstrate that cingulin participates in the modulation of endothelial barrier function both in human cultured cells in vitro and in mouse brains in vivo. Understanding the role of cingulin in maintaining tight barriers in endothelia may allow developing new strategies for the treatment of vascular leak syndromes. Abstract : Supplemental Digital Content is available in the text.